From consumption to production – development of fisheries and aquaculture in Portugal - Lopes, André Sobral de Castro (2016)
Seafood is considered an important element of a healthy diet; therefore, worldwide consumption has been increasing. This growth has been partly based in the development of the aquaculture industry, which contrasts with the depleted status of an increasing number of fish stocks worldwide. Countries with high seafood consumption rates tend to develop high seafood deficits, as well as an external seafood dependency. In Portugal, roughly 2/3 of availability is met by imports. In addition, seafood consumption rates are the highest in Europe; the combination of these two factors puts considerable pressure on the seafood trade balance and the production sector. Current consumption estimates only consider official availability data, by means of the apparent consumption method, which may induce errors in overall seafood consumption. Furthermore, the use of individual surveys has been shown to be a useful tool to obtain consumption data, regarding preferences and frequency of consumption. In order to estimate consumption, and the demand-based potential for an increase in production, a new methodology was developed. Official external trade volumes, as well as catch production and aquaculture yields, were combined with illegal fishing data, in order to estimate availability volumes. Therefore, through the integration of these estimates with the individual seafood consumption surveys, it was possible to estimate the growth potential of the aquaculture and fisheries sectors in Portugal. Eight products (cod, sardine, hake, horse mackerel, tuna, salmon, gilthead seabream and European seabass), which encompass between 63% and 71% of total seafood consumption, were identified as the most consumed. The unmet seafood demand was estimated to be between 13 396 and 41 024 tonnes, which corresponds to a potential growth of the current Portuguese seafood market of between 2.5% and 7.6%. The most promising areas identified were in the farmed fish sector. Other axes of intervention, such as the mitigation of illegal fishing or the improvement of the ecological status of fish stocks, were also identified as promising areas in order to increase overall seafood production.